Arte e Processos Colaborativos na Esfera Pública: a experiência do inSITE na região da fronteira entre México–Estados Unidos (Palíndromo, 2013)
Since 1992 inSITE has promoted the making of art projects across the public spaces of the border zone of San Diego (USA) and Tijuana (Mexico), having commissioned more than 200 projects, conceived by artists for the context of this region. In this article we investigated the inSITE construction process in the light of the new art practices in the public sphere, focusing on the contributions, hesitations and contradictions of its interaction with the border context. We aim to bring to the critical debate issues related to the production of art in public spaces today, such as community participation in the production of art, the role reserved for the public, the challenges artists face in attempting to respond to realities that are unfamiliar to them, and the continuous, tense negotiation among artists, curators and institutions.
Keywords: art; collaboration; community; public sphere